Calculation of Toric Intraocular Lens Power with the Barrett Calculator and Data from Three Keratometers - Jing Dong; Yaqin Zhang; Xiaogang Wang (Journal of Tropical Medicine)
Aim. To investigate the interdevice agreement for differences in toric power calculated using data on anterior corneal astigmatism obtained with corneal topography/ray-tracing aberrometry (iTrace), partial coherence interferometry (IOLMaster 500), and Scheimpflug imaging (Pentacam). Methods. The analysis included 101 eyes (101 subjects) with regular astigmatism. The main outcome measures were corneal cylinder power, axis of astigmatism, and keratometry values. Toricity and toric IOL power were calculated using the online Barrett toric calculator. Interdevice agreement for measurement and calculation was assessed using a paired sample t-test and a nonparametric test. Results. Significant interdevice differences were noted in the magnitude of astigmatism and flat, steep, and mean keratometry values between iTrace and IOLMaster (all P<0.01); in flat, steep, and mean keratometry values (all P<0.001) but not in the magnitude of astigmatism (P=0.325) between iTrace and Pentacam; and in the magnitude of astigmatism and steep and mean keratometry values (all P<0.01) but not in flat keratometry values (P=0.310) between IOLMaster and Pentacam. The toric IOL power calculated using data from the three devices showed the following trend: iTrace > IOLMaster (0.49 ± 0.36, P<0.001) and Pentacam (0.39 ± 0.42, P<0.001) and Pentacam was <IOLMaster (−0.10 ± 0.39, P=0.009). There were differences in toricity calculated using data from the three devices (P=0.004). Conclusions. Differences in toric IOL power and toricity calculated using anterior keratometry data from iTrace, IOLMaster 500, and Pentacam should be noted in clinical practice.